Mathematical Estimation of the Age of Mounds in Lithuania - Lukšienė, Daiva; Kanišauskas, Vaidotas (Jaunųjų mokslininkų darbai, 2017)
The aim of this paper is to develop a mathematical model for estimation of the age of mounds in Lithuania. On the grounds of archaeological literature it was found that mounds are of six periods. This study considers only these mounds that date back to a certain historical period. Using mathematical statistics and the α–normal distribution density function the database for the obtained parameters α and σ was formed. Having obtained empirical characteristics of these parameters the height and width of mounds of each period were found. Using the database of these parameters, the age of mounds can be easily determined, i.e. they can be attributed to some chronological period.